RNA interference and its role in the inhibition and cure of HIV/AIDS (Journal of Life and Earth Science, 2011)
The HIV/AIDS epidemic kills about 2.1 million people around the world every year. Unfortunately, until now attempts to control and diminish further spread of the disorder have resulted in very limited success. Although highly active antiretroviral therapy (HAART) is now available as a treatment option, the rate of its success is limited because of drug resistance. In this context, a more efficient treatment is very much necessary to fight with this fatal disease. The RNA interference (RNAi) can be employed as one of the powerful methods for treatment of the disease as it can effectively silence gene expression in a sequence specific manner. The RNAi-mediated treatment is therefore a promising substitution for therapy of the global epidemic HIV/AIDS in the future. The main objective of this review is to focus on an in-depth analysis of RNAi and the principles underlying RNAi treatment, and it’s also describes the molecular mechanisms of HIV infection, current treatment facilities available to patients as well as therapeutic applications of RNAi along with their limitations as to why the options are inadequate to give a safe and sound cure of HIV/AIDS.Key words: HIV/AIDS; RNA interference; treatments; limitationsDOI: 10.3329/jles.v5i0.7341J. Life Earth Sci., Vol. 5: 1-10, 2010